Empire of the Sun : Planets and Moons of the Solar System - Gribbin, John and Goodwin, Simon (London Constable, 1998)
Focusing on our Solar System this book contains many full page colour images of crater farms on Venus, the rings of Saturn, Jupiter and its moons, the tail of the Hale-Bopp comet, sunflares, Mars, cosmic debris and more. Detailed text accompanies each image, providing background information and maps to orient the reader.
Include Index, Appendix and Illustration
Keywords: Planets--Exploration -- Outer space -- Exploration of outer space